A conceptual model for action and design research - Henriques, T.; O'Neill, Henrique (World Conference on Qualitative Research, WCQR 2018, 2018)
Organizational research has a pattern of special characteristics which make a clear distinction from other research paradigms. When using these approaches – based on Action and Design – the Interpretivist, Constructivist, and Participatory perspectives dominate. They have already proven to have strong foundations, which turn these paradigmatic approaches into effective ways for getting knowledge, doing things, and promoting change within organizational settings. It combines the traditional scientific, engineering, and organization development approaches, depicting how an organization can, simultaneously, solve multidimensional problems and produce actionable knowledge, effective change and useful artifacts. It has been developed using a Design Science Research approach, tested in a major organizational change program (Henriques, 2015; Henriques & ONeill, 2014), and successfully used to teach research methods essentials to Master and DBA students.